Dielectric relaxation of vanadium-molybdenum tellurite glasses modified by alkaline-earth oxides - Terny, Cintia Soledad (2016)
Electrical response changes due to the incorporation of alkaline-earth oxides in the vanadium-molybdenum tellurite glassy matrix have been studied. The results are explained by analyzing the electric formalisms representations. A non-straightforward relationship to the modifier oxide ionic radius was found and the results suggest poor charge carrier interactions even at high alkaline-earth concentrations. The electrical behavior of the studied materials gives strong evidence that alkaline-earth modified tellurite glasses are poor candidates to become good ionic glassy conductors.